Spheric Aberration Evaluation of Thin Lens by Ray Transfer Matrix - Xuan Kien, Bui (VNU Journal of Science: Mathematics - Physics; Vol 40 No 3DO - 10.25073/2588-1124/vnumap.4946, 2024)
Spheric aberration is one of the optical aberrations influencing on the optical quality of the optical system, specially, the objective. In this work, we used the rays transfer matrix to evaluate the spheric aberration of the nonparaxial rays. Basing on the element configuration of the thin lens, we introduced the rays transfer matrix (RTM) describing the relation the object’s and image’s heigh from the optical axis. The transverse spheric aberration is numerically observed and compared to that obtained by using the paraxial approximation (PA). The obtained results are discussed to evaluate the spheric aberration of the thin lens, particularly, and the objective, generally.